2013
DOI: 10.1242/jeb.078519
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of succinate-fueled mitochondrial respiration in liver and skeletal muscle of hibernating thirteen-lined ground squirrels

Abstract: SUMMARYHibernating ground squirrels (Ictidomys tridecemlineatus) alternate between two distinct metabolic states throughout winter: torpor, during which metabolic rate (MR) and body temperature (T b ) are considerably suppressed, and interbout euthermia (IBE), during which MR and T b briefly return to euthermic levels. Previous studies showed suppression of succinate-fuelled respiration during torpor in liver and skeletal muscle mitochondria; however, these studies used only a single, saturating succinate conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Mitochondria isolated from the liver of torpid 13-lined ground squirrels exhibit state 3 respiration rates (near maximal respiration in the presence of saturating substrate and ADP) that are up to 70% lower than those from animals in IBE or summer euthermia (39,200). A similar, if less extreme, pattern is seen in liver mitochondria of Djungarian hamsters (40,167) and mice (42) that undergo daily torpor.…”
Section: Turning Down Atp Productionmentioning
confidence: 86%
“…Mitochondria isolated from the liver of torpid 13-lined ground squirrels exhibit state 3 respiration rates (near maximal respiration in the presence of saturating substrate and ADP) that are up to 70% lower than those from animals in IBE or summer euthermia (39,200). A similar, if less extreme, pattern is seen in liver mitochondria of Djungarian hamsters (40,167) and mice (42) that undergo daily torpor.…”
Section: Turning Down Atp Productionmentioning
confidence: 86%
“…Kinetic analysis of the succinate oxidation in hepatocytes mitochon dria was carried out upon low temperatures [2], hypoxia [12], immobilization stress [22], and upon the various physiological states [3]. Brown has revealed that the substrate oxi dation kinetics is modified during hibernation and it provides the metabolism regulation by mitochondria [3]. Priority use of succinate compared to the other substrates was noted in most works [2,3,18,19].…”
Section: Resultsmentioning
confidence: 99%
“…Brown has revealed that the substrate oxi dation kinetics is modified during hibernation and it provides the metabolism regulation by mitochondria [3]. Priority use of succinate compared to the other substrates was noted in most works [2,3,18,19]. Its oxidation rate is much higher in comparison with other sub strates of tricarboxylic acid cycle and the power of transmembrane potential generation is so large that supplies the maximal ADP phosphorylation intensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite this reversal, torpid respiration still remained four-fold lower than euthermic rates, indicating that inhibition of SDH by oxaloacetate does not account for the majority of suppression seen in torpor. Additionally, Brown et al (2013) found that while SDH activity was suppressed in torpor at 37°C, it was not suppressed when measured at 10°C, suggesting that SDH may contribute in the initiation of suppression, but does not maintain it. Finally, in both liver and skeletal muscle, torpid mitochondria have a greater affinity for succinate than euthermic mitochondria .…”
Section: Mitochondria and Cellular Respirationmentioning
confidence: 94%